Microstructure Changes of Cowhide and Properties of Wet Blue during Seawater Tanning Process - Kexin LIN; Lizhi HU; Ze NIU; Huitao WEN; Zhenhua TIAN (Pige Kexue Yu Gongcheng, 2024)
A wet-blue making process was designed using seawater instead of industrial water to obtain seawater processed cowhide (HS) wet blue. Using industrial water processed cowhide (GS) wet blue as the control group, the microstructure of HS during the process, and the thermal stability, sensory performance, and physical properties of the HS wet-blue were investigated. The results showed that the use of seawater had the greatest effect on the liming, and the collagen fibers in HS were less loose due to the inhibition effect of sodium chloride in seawater on the alkali swelling of HS limed hide. The chromium content of HS wet blue was lower than that of GS; additionally, HS wet blue has lower thermal stability, softness, and water permeability than those of GS wet-blue. Nevertheless, all indicators can meet the needs of the wet-blue making process. Meanwhile, the mechanical properties such as tensile strength, tear strength and burst strength were better than those of GS due to the more tightly woven of HS fibers; furthermore, the density and sensory performance of HS were slightly higher, which are reflective of the superiority of seawater used in wet-blue making process.